The Correlation between Transforming Growth Factor-Beta (TGF- β) Serum Level and Beck Depression Inventory (BDI) Score in Colorectal Cancer Patients at RSMH Palembang - Apriansyah, Muhammad Ali; Syahrir, Mediarty; Rosyidi, Muhammad, Kgs; Faisyar, Ahmad (UI Scholars Hub, 2020)
Introduction. Depression not only increase the mortality rate, but also can interfere the quality of life of colorectal cancer patients during treatment. Low levels of systemic inflammation may contribute to the development of depression. The inflammatory process can be seen by measuring serum transforming growth factor-β (TGF-β) levels and depressive symptoms using the beck depression inventory (BDI) score. This study aimed to determine the correlation between TGF-β serum levels with depression in colorectal cancer patients. Methods. Analytical observational research with cross sectional design was conducted among colorectal cancer patients who underwent chemotherapy with a BDI score ≥10 (depression) in the RSMH Palembang from June 2018 to June 2019. Serum TGF-β levels were measured by the enzyme-linked immunosorbent assay (ELISA) quantitative method. Spearman analysis was used to assess the correlation of TGF-β levels and BDI score. Results. A total of 40 subjects were included in this study with mean value of TGF-β serum was 108.14 pg/mL (SD 39.97 pg/mL). Median beck depression inventory (BDI) score was 14 (range 10-28). There was a moderate positive correlation between serum TGF-β levels and BDI score (r = 0.485; p = 0.002). Conclusion. There was a moderate positive correlation between serum TGF-β levels and BDI score in colorectal cancer patients at RSMH Palembang